Obesity and Clinical Outcomes of Acute Decompensated Heart Failure - Nuvus, Alviyatul Ainin; Andrianto, Andrianto; Mudjanarko, Sony Wibisono (Universitas Airlangga, 2025)
Highlights: Clinical outcomes in obese acute decompensated heart failure patients were found to be better than those of non-obese patients but not statistically significant. Acute decompensated heart failure patients were dominated by males. Abstract Introduction: Obesity is an independent risk factor that raises the prevalence of heart failure, but it is paradoxically associated with a better prognosis. This study examined the relationship between obesity and clinical outcomes of acute decompensated heart failure at Dr. Soetomo General Academic Hospital, Surabaya. Methods: This was an analytic observational study using a prospective cohort design. Patients with acute decompensated heart failure who were admitted to the inpatient care unit of Dr. Soetomo General Academic Hospital, Surabaya, from December 2021 to July 2022 were chosen using a purposive sample technique. The data were analyzed using the International Business Machines Corporation (IBM) Statistical Package for Social Sciences (SPSS) version 26.0. Results: There were 58 patients (n=58) representing different categories, with an average age of 55 years old, and were predominately males (58.6%). This study found that clinical outcomes in obese acute decompensated heart failure patients were better than those of non-obese patients in terms of shorter lengths of stay (p=0.825), lower rates of rehospitalization (p=0.458), and lower rates of all-cause mortality (p=0.673). Conclusion: The difference between the clinical outcomes in obese acute decompensated heart failure patients and non-obese patients was not statistically significant.